2018
DOI: 10.1177/0018578718778226
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacist Impact on Intensive Care Unit Delirium: Intervention and Monitoring

Abstract: The purpose of this study was to determine the impact of pharmacist monitoring with a clinical decision support system (CDSS) on clinical outcomes related to intensive care unit (ICU) delirium. Methods: This was a single-center, before-and-after study. This study compares patient outcomes of the preintervention group, which is the standard of care of pharmacist rounding, and the intervention group of pharmacy rounding with the CDSS rules. Using a CDSS, specific delirium risk factor rules were created to alert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…Considering other interventions, studies have evaluated pharmacist interventions involving sedative medications, as many patients in ICU facilities are prescribed sedatives to treat agitation in addition to analgesics to treat pain and/or antipsychotics to treat delirium 21,22 . Our study demonstrates that these interventions are numerous, accounting for more than 50% of total interventions.…”
Section: Resultsmentioning
confidence: 88%
“…Considering other interventions, studies have evaluated pharmacist interventions involving sedative medications, as many patients in ICU facilities are prescribed sedatives to treat agitation in addition to analgesics to treat pain and/or antipsychotics to treat delirium 21,22 . Our study demonstrates that these interventions are numerous, accounting for more than 50% of total interventions.…”
Section: Resultsmentioning
confidence: 88%
“…Key features of the included studies are shown in ►Table 3. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 included studies, 5 were randomized controlled trials, 27,30,31,33,34 6 were quasi-experimental, 22,25,28,29,32,35 2 were observational, 23,26 and 2 were cohort studies. 21,24 All of the studies had a control group and all 15 studies were deemed as good quality using the Newcastle-Ottawa Scale.…”
Section: Study Qualitymentioning
confidence: 99%
“…* Some of the studies are underpowered to detect a difference and do not show statistically significant outcomes. 31,33,56,69,70,72 Psychiatric pharmacists also show statistically significant benefits on patient-level outcomes in at least 5 peer-reviewed publications by providing services, including medication reviews, patient education, à patient and/or data evaluation for medication safety and efficacy, 26,31,35,37,40,41,47 and independent management of medication therapy upon referral. 50,[76][77][78][79]81 Twenty (31.3%) of the included studies have at least 1 BCPP author with formal advanced training in psychiatry/ neurology.…”
Section: Resultsmentioning
confidence: 99%